Geochemical Properties of Heavy Oil in Central Sumatra Basin - Desi Yensusnimar (Scientific Contributions Oil and Gas, 2021)
Heavyoilcommonly occurs due to biodegradation, whichmade the lighter fractiondisappears and then leaves the heavier fraction. Heavy oil is characterized by asphaltic, solid, and viscous because it contains asphalthene. Chemically, heavy oils contain fewer hydrogen atoms than light oils. Bulk properties ofheavy oil in addition to having a specific gravity of less than 25Â° API gravity, high viscosity, and often contain (concentration) of heavy metals (vanadium, nickel) which is higher than light oil (normal oil). Geochemical analysis based on the gas chromatography (GC) chromatogram of heavy oil in the Central Sumatra Basin shows a different pattern. The chromatogram pattern eliminates the light molecular fractions of the compounds in biodegraded oil and tar sand/bitumen. According to their geochemical properties, there are 4 (four) types of heavy oil in the Central Sumatra Basin namely: Type l come from shallow reservoir, water wash, and full biodegradation/all alkane depleted); Type 2 come from shallow reservoir, meteoric water, and light biodegradation, only low molecular weight alkane depleted); Type 3 come from deep reservoir, vertical gravity segregation, decreased weight fraction, can be caused by oil conditions in thick reservoirs, covered by impermeable lithology and usually located on the edge of the field (flank). Type 4 which contains medium-heavy oil (27Â°API) and is difficult to produce.